Get expert insights and community support for your questions on IDNLearn.com. Get the information you need from our community of experts, who provide detailed and trustworthy answers.

Which expression is equivalent to the given expression?

[tex]\( 2x^2 - 14x + 24 \)[/tex]

A. [tex]\( 2(x-5)(x-2) \)[/tex]

B. [tex]\( (2x-12)(x-2) \)[/tex]

C. [tex]\( 2(x-3)(x-4) \)[/tex]

D. [tex]\( 2(x-8)(x+3) \)[/tex]


Sagot :

To factor the quadratic expression [tex]\(2x^2 - 14x + 24\)[/tex], we need to find its roots and then write the expression in its factored form.

1. Identify Coefficients:
The quadratic expression is in the form [tex]\(ax^2 + bx + c\)[/tex], where:
- [tex]\(a = 2\)[/tex]
- [tex]\(b = -14\)[/tex]
- [tex]\(c = 24\)[/tex]

2. Calculate the Discriminant:
The discriminant of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is given by [tex]\(\Delta = b^2 - 4ac\)[/tex].

[tex]\[ \Delta = (-14)^2 - 4(2)(24) = 196 - 192 = 4 \][/tex]

3. Find the Roots:
The roots of the quadratic equation can be found using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{\Delta}}{2a}\)[/tex].

[tex]\[ x = \frac{14 \pm \sqrt{4}}{4} = \frac{14 \pm 2}{4} \][/tex]

This gives us two roots:
[tex]\[ x_1 = \frac{14 + 2}{4} = \frac{16}{4} = 4 \][/tex]
[tex]\[ x_2 = \frac{14 - 2}{4} = \frac{12}{4} = 3 \][/tex]

4. Write the Factored Form:
With the roots [tex]\(x_1 = 4\)[/tex] and [tex]\(x_2 = 3\)[/tex], the quadratic expression can be factored as:
[tex]\[ 2(x - 4)(x - 3) \][/tex]

So, the factored form of the expression [tex]\(2x^2 - 14x + 24\)[/tex] is [tex]\(2(x - 4)(x - 3)\)[/tex], which corresponds to option:

C. [tex]\(2(x - 3)(x - 4)\)[/tex]

(Note that since multiplication is commutative, both [tex]\(2(x-4)(x-3)\)[/tex] and [tex]\(2(x-3)(x-4)\)[/tex] are correct and equivalent.)